(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The National Rural Employment Guarantee Act 2005 (No 42),also known as the "Mahatma Gandhi National Rural Employment GuaranteeAct", and abbreviated to MGNREGA, is an Indianlabour law and socialsecurity measure that aims to guarantee the ’rightto work’ and ensure livelihood security in ruralareas by providing at least 100 days of guaranteed wage employment in afinancial year to every household whose adult members volunteer to do unskilledmanual work. The UPA Government had planned to increase the number ofworking days from 100 to 150 before the 2014 Lok Sabha Elections in the countrybut failed. The statute is hailed by the government as "the largestand most ambitious social security and public works programme in theworld". The more comprehensive survey of Comptroller andAuditor General (CAG) of India, a ‘Supreme AuditInstitution’ defined in Article 148 of the Constitution of India,reports serious lapses in implementation of the act.